2021
DOI: 10.1093/aobpla/plab034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the contribution of osmotic and oxidative stress components on barley growth under salt stress

Abstract: Salt stress is considered one of the most devastating environmental stresses, affecting barley growth and leading to significant yield loss. Hence, there is considerable interest in investigating the most effective traits that determine barley growth under salt stress. The objective of this study was to elucidate the contribution of osmotic and oxidative stress components in leaves and roots growth under salt stress. Two distinct barley (Hordeum vulgare L.) salt-stress tolerant genotypes, Barrage-Malleg (BM, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 47 publications
1
9
0
1
Order By: Relevance
“…The bud length was also inhibited with the increase in compound salt concentration. This is consistent with the results of Nefissi Ouertani et al [27,28]. Salt stress caused plant metabolism disorder, disrupted development, decreased the net photosynthetic rate and increased activities of antioxidant enzymes [29,30].…”
Section: Germinationsupporting
confidence: 92%
“…The bud length was also inhibited with the increase in compound salt concentration. This is consistent with the results of Nefissi Ouertani et al [27,28]. Salt stress caused plant metabolism disorder, disrupted development, decreased the net photosynthetic rate and increased activities of antioxidant enzymes [29,30].…”
Section: Germinationsupporting
confidence: 92%
“…The destructive effect of salt stress on lipid peroxidation has already been shown by Zeeshan et al (2020) who found a higher MDA content in salt-tolerant than salt-sensitive genotype and that MDA can potentially be used as an indicator of salt tolerance in wheat and barley. Nefissi Ouertani et al (2021) also observed an association between low MDA content and higher salt-stress tolerance in barley.…”
Section: Discussionmentioning
confidence: 67%
“…However, it was possible to identify lines that showed high rates of root growth in both medium and high salinities, some due to having high levels of root growth in control conditions, such as Floye, and others despite not, such as Bere 49 A 27 Shetland. The latter of these are of most interesting as it has been shown that the maintenance of root elongation, in saline conditions that inhibit the normal shoot growth of the seedling, is indicative of an adaptive method to safeguard uptake of nutrients and water ( Shelden et al, 2020 ), with other experiments showing salinity tolerant lines having shorter roots in control conditions but maintaining them in saline conditions ( Adjel et al, 2013 ; Nefissi Ouertani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%